Acoustic stimulation causes tonotopic alterations in the length of isolated outer hair cells from guinea pig hearing organ. - Canlon, B (1988)
Isolated outer hair cells from the mammalian cochlea exhibit a motile response to electrical or chemical stimulation. Here we show that isolated outer hair cells can also respond to acoustic stimulation, in the form of a tone burst of 200 Hz, by either shortening or lengthening depending on their cochlear location. Cells from the apical region of the cochlea (long cells) responded by increasing their length, whereas those from more basal regions (short cells) responded by decreasing their length. Cells from intermediate positions showed an equal probability for either elongating or shortening. Both the elongating and shortening response was inhibited by 3 microM poly(L-lysine). It is suggested that this tonotopic and bidirectional acoustic response may be one of the active components underlying the specific phase and frequency displacement of the basilar membrane.